SOFC high-temperature vermiculite sealing material and preparation method thereof

Through electrostatic attraction composite modified chemically expanded vermiculite and negative ion high-temperature expanded vermiculite, a high-temperature vermiculite sealing material without adhesive is formed, which solves the problems of large amount of adhesive and high firing loss, and achieves improvement of sealing performance and high temperature stability.

CN119864440AActive Publication Date: 2025-04-22ZHEJIANG CPS CATHAY PACKING & SEALING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411933486.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-22
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The amount of adhesive used and the amount of burning loss in existing high-temperature vermiculite sealing materials leads to a reduction in sealing performance.

Method used

Modified chemically expanded vermiculite and negative ion high-temperature expanded vermiculite are combined by electrostatic attraction to form a sealing material without adhesives. Modified chemically expanded vermiculite has a positive charge, and negative ion high-temperature expanded vermiculite has a negative charge. After the two are mixed, electrostatic attraction is generated to achieve recombination.

Benefits of technology

While not changing the composite strength of the sealing material, it significantly reduces the fever loss and improves the sealing performance, and the material has stronger stability in high temperature environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of sealing materials, and discloses an SOFC high-temperature vermiculite sealing material and a preparation method thereof.The material is prepared from modified chemical expanded vermiculite and anion high-temperature expanded vermiculite, the modified chemical expanded vermiculite carries positive charges, and the anion high-temperature expanded vermiculite carries negative charges; the two materials are mixed to generate electrostatic attraction so as to realize compounding, the material does not use an adhesive, and the ignition loss is remarkably reduced while the compounding strength of the sealing material is not changed; the fatty acid salt is used as an intercalation agent of the chemical expanded vermiculite, and the modified chemical expanded vermiculite prepared from the fatty acid salt has the high-temperature-resistant compressive strength of 700 DEG C; according to the anion high-temperature expanded vermiculite, anion air is adopted for treating the high-temperature expanded vermiculite, so that the high-temperature expanded vermiculite loads and accumulates negative charges, chemical agents are not needed when the anion air is used for treating the high-temperature expanded vermiculite, the process is simple, and large-scale production can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sealing materials, and in particular to a SOFC high-temperature vermiculite sealing material and a preparation method thereof. Background Art

[0002] Solid oxide fuel cell (SOFC) is an energy conversion device that directly converts fuel chemical energy into electrical energy. It is not limited by the Carnot cycle, has high energy conversion efficiency, and has the advantages of wide fuel adaptability, clean and pollution-free, all-solid-state structure, and no use of precious metal catalysts. The stack is the core component of SOFC, which is sealed with stack sealing materials. At present, the stack sealing materials in the prior art are mainly high-temperature glass glue and high-temperature ceramic glue. The thermal expansion coefficients of glass, metal and battery cells are different. Under the working conditions of high temperature, current, and airflow disturbance, the stack sealing structure is easily damaged, resulting in performance degradation, and the number of times the stack is started and stopped is severely restricted. Therefore, it is necessary to provide a new stack sealing material.

[0003] A sealing material disclosed in publication number CN112424310 B points out that high-temperature vermiculite sealing material has extremely stable characteristics such as high thermal cycle resistance, high temperature resistance and corrosion resistance, and is an excellent SOFC sealing material. At present, the traditional high-temperature vermiculite sealing material is formed by bonding chemical expanded vermiculite and high-temperature expanded vermiculite with a polymer binder. Since the polymer binder is mainly an organic polymer, it will carbonize under high temperature conditions, which makes the loss on ignition of the high-temperature sealing material increase with the increase in the amount of polymer binder. Excessive loss on ignition will cause the structure of the sealing material to collapse easily and the sealing performance to be significantly reduced. Therefore, when preparing the high-temperature vermiculite sealing material, it is necessary to balance the relationship between the bonding strength and the loss on ignition, and minimize the loss on ignition while ensuring the strength of the sealing material. Summary of the invention

[0004] In order to overcome the problem of large amount of binder and high ignition loss in the high-temperature vermiculite sealing material in the prior art, the present invention provides a SOFC high-temperature vermiculite sealing material and a preparation method thereof. The material is made of modified chemical expanded vermiculite and negative ion high-temperature expanded vermiculite. The modified chemical expanded vermiculite has a positive charge, and the negative ion high-temperature expanded vermiculite has a negative charge. After the two are mixed, electrostatic attraction is generated to achieve compounding. The material does not use an adhesive, and the ignition loss is significantly reduced without changing the composite strength of the sealing material.

[0005] The specific technical scheme of the present invention is: A SOFC high-temperature vermiculite sealing material, the raw materials of which include modified chemically expanded vermiculite and negative ion high-temperature expanded vermiculite, the raw materials of the modified chemically expanded vermiculite include stearate and chemically expanded vermiculite, the mass ratio of stearate to chemically expanded vermiculite is 3-5:1, and the raw materials of the negative ion high-temperature expanded vermiculite are negative ion air and high-temperature expanded vermiculite.

[0006] The present invention provides a SOFC high-temperature vermiculite sealing material, which is compounded by positively charged modified chemical expanded vermiculite and negatively charged anion high-temperature expanded vermiculite through electrostatic attraction. Compared with the traditional high-temperature vermiculite sealing material compounded with a binder, the composite strength does not change significantly, and the ignition loss is significantly reduced.

[0007] The modified chemical expanded vermiculite of the present invention adopts stearate intercalation agent to carry out intercalation modification on the chemical expanded vermiculite. The chemical expanded vermiculite has the characteristic of interlayer charge accumulation, so a cation exchanger can be used to carry out intercalation modification on the chemical expanded vermiculite. After the positive charge is accumulated, the interlayer spacing of the expanded vermiculite after intercalation modification is increased. Commonly used cation exchangers mainly include quaternary ammonium salt cation exchangers, and the present invention actually finds that the quaternary ammonium salt cation exchangers used in traditional sealing materials have the problem of being easy to decompose at high temperature during use, which leads to the composite modified chemical expanded vermiculite and negative ion high temperature expanded vermiculite using electrostatic attraction to fail quickly under high temperature environment, resulting in the collapse of the sealing material structure. Therefore, in view of the above problems, the present application selects stearate as the intercalation agent of the chemical expanded vermiculite, and the modified chemical expanded vermiculite made by using the stearate has a high temperature resistant compressive strength of 700°C.

[0008] The negative ion high temperature expanded vermiculite of the present invention uses negative ion air to treat the high temperature expanded vermiculite so that the high temperature expanded vermiculite is loaded with and accumulates negative charges. The use of negative ion air to treat the high temperature expanded vermiculite does not require the use of chemical agents and has a simple process and can be mass-produced.

[0009] Preferably, the mass ratio of the modified chemically expanded vermiculite to the negative ion high temperature expanded vermiculite is 2 to 4:1.

[0010] Preferably, the concentration of negative ions in the negative ion air is 10000 to 15000 / cm 3 .

[0011] Preferably, the chemically expanded vermiculite has a mesh size of 20 to 50.

[0012] Preferably, the particle size of the high temperature expanded vermiculite is 300-325 meshes.

[0013] A preparation method of the above-mentioned SOFC high-temperature vermiculite sealing material comprises the following steps: injecting stearate and chemically expanded vermiculite into a ball milling device for ball milling to obtain modified chemically expanded vermiculite, passing air into a high-pressure ionization chamber for negative high-pressure ionization to obtain negative ion air, passing the negative ion air into a filter element filled with high-temperature expanded vermiculite for filtering to obtain negative ion high-temperature expanded vermiculite, and mixing the modified chemically expanded vermiculite and the negative ion high-temperature expanded vermiculite to uniformly stir and pressurize to obtain the SOFC high-temperature vermiculite sealing material.

[0014] The present invention also provides a method for preparing the above-mentioned SOFC high-temperature vermiculite sealing material. In the method, the negative ion high-temperature vermiculite is prepared by using negative ion air and high-temperature expanded vermiculite. The negative ion air is prepared by ionizing air in a high-voltage electrostatic chamber. The air generates negative ions after being treated with high-voltage electrostatics. The negative ion air is then passed into a filter element made of high-temperature expanded vermiculite. Through the filtering effect of the high-temperature expanded vermiculite, the negative ions in the air are loaded onto the high-temperature expanded vermiculite, so that the high-temperature expanded vermiculite accumulates negative charges. The method does not require the use of chemical agents to prepare the negative ion high-temperature expanded vermiculite, and the process is simple and can be mass-produced.

[0015] Preferably, the pressure of the press molding is 5 to 10 MPa and the time is 1 to 3 hours.

[0016] Preferably, the ball milling speed is 50-80 rpm and the time is 1-2 hours.

[0017] Preferably, the voltage of the high-voltage ionization treatment is 10000-12000V.

[0018] Preferably, the flow rate of negative ion air is 100-200 cm 3 / min, the filtration treatment time is 3 to 5 hours, and the mass of high-temperature expanded vermiculite is 0.8 to 1 kg.

[0019] Compared with the prior art, this application has the following technical effects: (1) The material is made of modified chemical expanded vermiculite and negative ion high temperature expanded vermiculite. The modified chemical expanded vermiculite has a positive charge, and the negative ion high temperature expanded vermiculite has a negative charge. When the two are mixed, electrostatic attraction is generated to achieve compounding. The material does not use adhesives, and the loss on ignition is significantly reduced without changing the composite strength of the sealing material; (2) Stearate is used as an intercalant for chemically expanded vermiculite. The modified chemically expanded vermiculite made with the stearate has a high temperature resistant compressive strength of 700°C; (3) The negative ion high temperature expanded vermiculite of the present invention uses negative ion air to treat the high temperature expanded vermiculite so that the high temperature expanded vermiculite is loaded with and accumulates negative charges. The use of negative ion air to treat the high temperature expanded vermiculite does not require the use of chemical agents and has a simple process and can be mass-produced. DETAILED DESCRIPTION

[0020] The present invention will be further described below in conjunction with the embodiments.

[0021] Embodiment 1: A method for preparing a SOFC high-temperature vermiculite sealing material comprises the following steps: Step 1: 1L of anhydrous ethanol, 300g of zinc stearate and 100g of chemically expanded vermiculite (20-50 meshes) are added to a ball mill, the ball mill is heated to 60°C and then ball milled at a speed of 50rmp for 1h to prepare a wet material, and after the wet material is cooled, it is rinsed with deionized water and placed in an oven at 80°C to dry to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply a 10,000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 10,000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 0.8kg high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 100cm 3 / min, the filtration treatment time is 3h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 2:1, and place the mixture in a mold for pressure molding at a pressure of 5 MPa for 3 hours to prepare a SOFC high temperature vermiculite sealing material.

[0022] Embodiment 2: A method for preparing a SOFC high-temperature vermiculite sealing material comprises the following steps: Step 1: Add 1L of anhydrous ethanol, 400g of zinc stearate and 100g of chemically expanded vermiculite (20-50 meshes) into a ball mill, heat the ball mill to 70°C, and perform ball milling at a speed of 70rmp for 1-2h to prepare a wet material, and after the wet material is cooled, rinse it with deionized water and dry it in an oven at 80°C to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply 11000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 12000 / cm 3The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 0.9 kg of high temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high temperature expanded vermiculite. The air flow rate is 150 cm 3 / min, the filtration treatment time is 4h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 3:1, and place the mixture in a mold for pressure molding at a pressure of 8 MPa for 2 hours to prepare a SOFC high temperature vermiculite sealing material.

[0023] Embodiment 3: A method for preparing a SOFC high-temperature vermiculite sealing material comprises the following steps: Step 1: Add 1L of anhydrous ethanol, 500g of zinc stearate and 100g of chemically expanded vermiculite (20-50 meshes) into a ball mill, heat the ball mill to 80°C, and perform ball milling at a speed of 80rmp for 1-2h to prepare a wet material, and after the wet material is cooled, rinse it with deionized water and dry it in an oven at 80°C to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply 12000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 15000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 1kg of high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 200cm 3 / min, the filtration treatment time is 5h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 5:1, and place the mixture in a mold for pressure molding at a pressure of 10 MPa for 1 hour to prepare a SOFC high temperature vermiculite sealing material.

[0024] Embodiment 4: A method for preparing a SOFC high-temperature vermiculite sealing material comprises the following steps: Step 1: 1L of anhydrous ethanol, 400g of zinc stearate and 100g of chemically expanded vermiculite (20-50 meshes) are added to a ball mill, the ball mill is heated to 80°C and then ball milled at a speed of 80rmp for 1h to prepare a wet material, the wet material is cooled, rinsed with deionized water and dried in an oven at 80°C to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply a 10,000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 10,000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 1kg of high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 100cm 3 / min, the filtration treatment time is 5h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 3:1, and place the mixture in a mold for pressure molding at a pressure of 10 MPa for 1 hour to prepare a SOFC high temperature vermiculite sealing material.

[0025] Embodiment 5: A method for preparing a SOFC high-temperature vermiculite sealing material comprises the following steps: Step 1: 1L of anhydrous ethanol, 400g of zinc stearate and 100g of chemically expanded vermiculite (20-50 meshes) are added to a ball mill, the ball mill is heated to 80°C and then ball milled at a speed of 80rmp for 1h to prepare a wet material, the wet material is cooled, rinsed with deionized water and dried in an oven at 80°C to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply a 10,000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 15,000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 1kg of high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 200cm 3 / min, the filtration treatment time is 5h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 3:1, and place the mixture in a mold for pressure molding at a pressure of 10 MPa for 1 hour to prepare a SOFC high temperature vermiculite sealing material.

[0026] Embodiment 6: A method for preparing a SOFC high-temperature vermiculite sealing material comprises the following steps: Step 1: Add 1L of anhydrous ethanol, 400g of zinc stearate and 100g of chemically expanded vermiculite (20-50 meshes) into a ball mill, heat the ball mill to 60-80°C, and then perform ball milling at a speed of 50-80rmp for 1-2h to prepare a wet material, and after the wet material is cooled, rinse it with deionized water and dry it in an oven at 80°C to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply 12000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 15000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 1kg of high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 200cm 3 / min, the filtration treatment time is 3h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 3:1, and place the mixture in a mold for pressure molding at a pressure of 10 MPa for 1 hour to prepare a SOFC high temperature vermiculite sealing material.

[0027] Comparative Example 1: Compared with Example 1, in Comparative Example 1, an organic polymer binder SOFC high temperature vermiculite sealing material is used, and the organic polymer binder is, comprising the following steps: Step 1: 1L of anhydrous ethanol, 300g of zinc stearate and 100g of chemically expanded vermiculite (20-50 meshes) are added to a ball mill, the ball mill is heated to 60°C and then ball milled at a speed of 50rmp for 1h to prepare a wet material, and after the wet material is cooled, it is rinsed with deionized water and placed in an oven at 80°C to dry to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply a 10,000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 10,000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 0.8kg high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 100cm 3 / min, the filtration treatment time is 3h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: vacuum knead and mix the modified chemical expanded vermiculite, negative ion high temperature expanded vermiculite and binder in a mass ratio of 2:1:0.05, place the mixture in a mold for pre-forming and dry the blank at 70°C, place the blank on a hot press vulcanizer for hot pressing and vulcanization to form SOFC high temperature vermiculite sealing material.

[0028] Comparative Example 2: Compared with Example 1, in Comparative Example 2, a quaternary ammonium salt cation exchanger is used to modify the chemically expanded vermiculite, and the quaternary ammonium salt cation exchanger is octadecyltrimethylammonium bromide, comprising the following steps:.

[0029] A method for preparing a SOFC high-temperature vermiculite sealing material comprises the following steps: Step 1: 1L of water, 300g of octadecyltrimethylammonium bromide and 100g of chemically expanded vermiculite (20-50 meshes) are added to a ball mill, the ball mill is heated to 60°C and then ball milled at a speed of 50rmp for 1h to prepare a wet material, the wet material is cooled, rinsed with deionized water and dried in an oven at 80°C to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply a 10,000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 10,000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 0.8kg high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 100cm 3 / min, the filtration treatment time is 3h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 2:1, and place the mixture in a mold for pressure molding at a pressure of 5 MPa for 3 hours to prepare a SOFC high temperature vermiculite sealing material.

[0030] Comparative Example 3: Compared with Example 1, in Comparative Example 3, a quaternary ammonium salt cation exchanger is used to modify the chemically expanded vermiculite, wherein the quaternary ammonium salt cation exchanger is hexadecyltrimethylammonium bromide, and the method comprises the following steps: A method for preparing a SOFC high-temperature vermiculite sealing material comprises the following steps: Step 1: 1L of water, 300g of hexadecyltrimethylammonium bromide and 100g of chemically expanded vermiculite (20-50 meshes) are added to a ball mill, the ball mill is heated to 60°C and then ball milled at a speed of 50rmp for 1h to prepare a wet material, the wet material is cooled, rinsed with deionized water and dried in an oven at 80°C to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply a 10,000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 10,000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 0.8kg high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 100cm 3 / min, the filtration treatment time is 3h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 2:1, and place the mixture in a mold for pressure molding at a pressure of 5 MPa for 3 hours to prepare a SOFC high temperature vermiculite sealing material.

[0031] Comparative Example 4: Compared with Example 1, in Comparative Example 4, the stearate is calcium stearate, comprising the following steps: Step 1: 1L of anhydrous ethanol, 300g of calcium stearate and 100g of chemically expanded vermiculite (20-50 meshes) are added to a ball mill, the ball mill is heated to 60°C and then ball milled at a speed of 50rmp for 1h to prepare a wet material, the wet material is cooled, rinsed with deionized water and placed in an oven at 80°C to dry to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply a 10,000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 10,000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 0.8kg high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 100cm 3 / min, the filtration treatment time is 3h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 2:1, and place the mixture in a mold for pressure molding at a pressure of 5 MPa for 3 hours to prepare a SOFC high temperature vermiculite sealing material.

[0032] Comparative Example 5: Compared with Example 1, in Comparative Example 5, the stearate is barium stearate, and the steps are as follows: Step 1: 1L of anhydrous ethanol, 300g of barium stearate and 100g of chemically expanded vermiculite (20-50 meshes) are added to a ball mill, the ball mill is heated to 60°C and then ball milled at a speed of 50rmp for 1h to prepare a wet material, the wet material is cooled, rinsed with deionized water and dried in an oven at 80°C to prepare a modified chemically expanded vermiculite; Step 2: Pass the air into the high-voltage electrostatic chamber and apply a 10,000V voltage to the electrodes to ionize the air into negative ion air. The concentration of negative ions in the negative ion air is 10,000 / cm 3 The negative ion air is input into the air filter through the output pump. The filter element of the air filter is filled with 0.8kg high-temperature expanded vermiculite (300-325 mesh). The air filter is used to process the negative ion air to make negative ion high-temperature expanded vermiculite. The air flow rate is 100cm 3 / min, the filtration treatment time is 3h, and after the treatment, the negative ion high temperature expanded vermiculite in the air filter element is collected; Step 3: Mix and stir the modified chemical expanded vermiculite and the negative ion high temperature expanded vermiculite in a mass ratio of 2:1, and place the mixture in a mold for pressure molding at a pressure of 5 MPa for 3 hours to prepare a SOFC high temperature vermiculite sealing material.

[0033] Comparative Example 6: Compared with Example 1, the mass ratio of zinc stearate to chemically expanded vermiculite in Comparative Example 6 is 0.5:1, and the other conditions are the same as those in Example 1.

[0034] Comparative Example 7: Compared with Example 1, the mass ratio of zinc stearate to chemically expanded vermiculite in Comparative Example 7 is 10:1, and the other conditions are the same as those in Example 1.

[0035] Test example: The ignition loss, tensile strength, density and high temperature compressive strength properties of the SOFC high temperature vermiculite sealing materials obtained in Examples 1 to 6 and Comparative Examples 1 to 7 were tested; The loss on ignition is tested according to the method disclosed in GB / T 27970-2011 Test method for burning vector of non-metallic gasket materials, with a temperature of 800°C and a time of 4 hours; The tensile strength test is carried out according to the method disclosed in GB / T 20671.7-2006 Classification system and test methods for non-metallic gasket materials; High temperature compressive strength The SOFC high temperature vermiculite sealing material was tested using a high temperature compressive testing machine to test the temperature at which the SOFC high temperature vermiculite sealing material was destroyed. The test results are shown in Table 1.

[0036] Table 1 Test results <![CDATA[Density (g / cm 3 )]]> Loss on ignition (%) Tensile strength(Mpa) High temperature compressive strength(℃) Example 1 1.03 4.82 0.49 700 Example 2 1.08 4.74 0.48 700 Example 3 1.05 4.85 0.49 700 Example 4 1.02 4.83 0.48 700 Example 5 1.04 4.82 0.49 700 Example 6 1.02 4.82 0.48 700 Comparative Example 1 1.03 6.82 / 350 Comparative Example 2 / / / 250 Comparative Example 3 / / / 180 Comparative Example 4 / / / 400 Comparative Example 5 / / / 300 Comparative Example 6 / / 0.23 / Comparative Example 7 / / 0.49 / As shown in Table 1, the thermal weight loss of the SOFC high temperature vermiculite sealing materials prepared in Examples 1 to 6 is less than 5%, the tensile strength is less than 0.5 MPa, and the density is 1.0±1 g / cm 3 The high temperature resistant compressive strength can reach 700°C. The above results show that the SOFC high temperature vermiculite sealing material prepared by the present invention has low ignition loss and excellent high temperature resistance and excellent sealing performance.

[0037] Comparative Example 1 is a SOFC high-temperature vermiculite sealing material made by compounding with an adhesive. The loss on ignition of Comparative Example 1 is 6.82%, and the high-temperature compressive strength is 350°C. Compared with Example 1, the loss on ignition of Comparative Example 1 is significantly higher than that of Example 1, and the high-temperature compressive performance is significantly lower than that of Example 1. The above results show that the SOFC high-temperature vermiculite sealing material prepared by the present invention has a significantly reduced loss on ignition and significantly increased high-temperature compressive performance compared with the adhesive composite material. Since the adhesive is usually an organic polymer, the high-temperature resistance of the adhesive is low. The adhesive component will soften or even decompose in a high-temperature environment, resulting in leakage of the sealing material and other problems. The high-temperature vermiculite material of the present application adopts electrostatic attraction and has stronger stability in a high-temperature environment.

[0038] Comparative Examples 2 and 3 respectively use quaternary ammonium salt cation exchangers octadecyl trimethyl ammonium bromide and hexadecyl trimethyl ammonium bromide to treat chemically expanded graphite. The results show that the high temperature compressive strength of Comparative Example 2 is 250°C, and the high temperature compressive strength of Comparative Example 3 is 180°C. The high temperature compressive strengths of Comparative Examples 2 and 3 are significantly lower than those of Example 1. After analysis, it is found that the quaternary ammonium salt cation exchanger inserted into the vermiculite will decompose at high temperature, resulting in the electrostatic attraction of the vermiculite of the SOFC high temperature vermiculite sealing material in a high temperature environment. Rapid failure due to the decomposition of the quaternary ammonium salt cation exchanger causes the material to collapse.

[0039] Comparative Examples 4 and 5 respectively used calcium stearate and barium stearate to treat the chemically expanded graphite. The results showed that the high temperature compressive strength of Comparative Example 4 was 400°C, and the high temperature compressive strength of Comparative Example 5 was 300°C. The high temperature compressive strengths of Comparative Examples 4 and 5 were significantly lower than those of Example 1. Analysis showed that calcium stearate and barium stearate also thermally decomposed at high temperatures. However, since the temperature of the heating stack will exceed 500°C, in order to ensure that the high temperature resistance of the sealing material can meet the use requirements of the stack, the stack needs to be further optimized. From the above content, it can be seen that when using a cation exchanger chemically expanded vermiculite for modification, it is necessary to select a material that is not easily decomposed at high temperature to ensure that the electrostatic attraction of the SOFC high temperature vermiculite sealing material will not fail due to the decomposition of the cation exchanger. Therefore, the type of cation exchanger can be adjusted according to the needs of actual applications.

[0040] Comparative Examples 6 and 7 respectively investigated the dosage of zinc stearate and chemically expanded vermiculite. The results showed that too small a dosage resulted in insufficient positive charge on the modified chemically expanded vermiculite, and the tensile strength of the SOFC high-temperature vermiculite sealing material was reduced. When the dosage was too large, due to the saturation of the intercalation effect of the intercalant, when a certain amount was reached, the intercalant could not be inserted into the vermiculite layers, resulting in excessive use of zinc stearate not improving the material performance.

[0041] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.

Claims

1. A SOFC high temperature vermiculite sealing material, characterized in that: The raw materials include modified chemical expanded vermiculite and negative ion high temperature expanded vermiculite. The raw materials of the modified chemical expanded vermiculite include stearate and chemical expanded vermiculite, the mass ratio of zinc stearate to chemical expanded vermiculite is 3-5:1, and the raw materials of the negative ion high temperature expanded vermiculite are negative ion air and high temperature expanded vermiculite.

2. The SOFC high temperature vermiculite sealing material according to claim 1, characterized in that: The mass ratio of modified chemical expanded vermiculite to negative ion high temperature expanded vermiculite is 2~4:

1.

3. The SOFC high temperature vermiculite sealing material according to claim 1, characterized in that: The concentration of negative ions in negative ion air is 10000~15000 / cm 3 .

4. The SOFC high temperature vermiculite sealing material according to claim 1, characterized in that: The chemically expanded vermiculite has a mesh size of 20 to 50.

5. The SOFC high temperature vermiculite sealing material according to claim 1, characterized in that: The particle size of the high temperature expanded vermiculite is 300-325 mesh.

6. A method for preparing a SOFC high temperature vermiculite sealing material according to any one of claims 1 to 5, characterized in that: The following steps are involved: Stearate and chemically expanded vermiculite are injected into a ball mill for ball milling to obtain modified chemically expanded vermiculite, air is passed into a high-pressure ionization chamber for high-pressure ionization to obtain negative ion air, the negative ion air is passed into a filter element filled with high-temperature expanded vermiculite for filtration to obtain negative ion high-temperature expanded vermiculite, the modified chemically expanded vermiculite and the negative ion high-temperature expanded vermiculite are mixed and stirred uniformly and pressurized to obtain SOFC high-temperature vermiculite sealing material.

7. The preparation method according to claim 6, characterized in that: The pressure of the press molding is 5-10 MPa.

8. The preparation method according to claim 6 or 7, characterized in that: The time of the press molding is 1 to 3 hours.

9. The preparation method according to claim 6, characterized in that: The ball milling speed is 50-80 rpm and the time is 1-2 h.

10. The preparation method according to claim 6, characterized in that: The voltage of the high-voltage ionization treatment is 10000-12000 V, and the flow rate of the negative ion air is 100-200 cm 3 / min, the filtration treatment time is 3~5 h, and the mass of high-temperature expanded vermiculite is 0.8~1 kg.

Citation Information

Patent Citations

  • Sealing material

    CN112424310B

  • Preparation method and preparation device for high-temperature vermiculite sealing materials

    CN107722515A

  • Sealing material

    CN112424310A

  • Nonaqueous cell with improved thermoplastic sealing member

    CN1864285A

  • Method of generating subscription information, and device thereof

    KR1020230064529A